Chemical composition, sensory properties and application of Sichuan pepper (Zanthoxylum genus) - Yue Jie; Shiming Li; Chi-Tang Ho (Food Science and Human Wellness)
This review summarized the composition of volatile and nonvolatile compounds, the sensory mechanism and the application of Sichuan pepper (Zanthoxylum genus) as a spice and multifunctional food, such as antibacterial, inhibition of inflammation, and antioxidant among others. The aim is to provide a better understanding and potential future in-depth research and application of Sichuan pepper. Keywords: Sichuan pepper, Zanthoxylum, Volatile flavor compounds, Pungent taste, Alkyl amides